2011
DOI: 10.1267/ahc.11013
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Temporary Expressions of Smooth Muscle Actin in Hair, Vibrissa, Arrector Pili Muscle, and Other Hair Appendages of Developing Rats

Abstract: The hair erection muscle, arrector pili, is a kind of smooth muscle located in the mammalian dermis. The immunohistochemical study using an antibody against smooth muscle alpha actin (SMA) showed that the arrector pili muscle develops approximately 1–2 weeks after birth in dorsal and ventral skin, but thereafter they degenerate. The arrector pili muscle was not detected in the mystacial pad during any stage of development, even in the neighboring pelage-type hair follicle. A strong signal of SMA in the skin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…10,11 The APM connects the bulge region of a permanent portion of the hair follicle to the dermis and is innervated by adrenergic neurons, which are classified as sympathetic neurons. 12,13 Recently, it was reported that the embryonic hair follicle bud could function as a guide for migration of sense neurons in vivo and in vitro and that nephronectin-expressing follicular epithelial stem cells provide the niche for APM development and define the positioning of the follicular muscular junction. 10,14 However, functional restoration and re-innervation of APM of adult hair follicles are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The APM connects the bulge region of a permanent portion of the hair follicle to the dermis and is innervated by adrenergic neurons, which are classified as sympathetic neurons. 12,13 Recently, it was reported that the embryonic hair follicle bud could function as a guide for migration of sense neurons in vivo and in vitro and that nephronectin-expressing follicular epithelial stem cells provide the niche for APM development and define the positioning of the follicular muscular junction. 10,14 However, functional restoration and re-innervation of APM of adult hair follicles are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…3 F and is positive for γ-SMA, and is also positive for γ-CYA ( Fig. 3 C), α-SKA [ 22 ], and α-SMA [ 21 ]. The sections in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results showed that α-SMA expression in the arrector pili muscle of the rat had been mostly observed during the neonatal period [ 21 ]. The present experiment shows that γ-SMA became detectable in the arrector pili muscle of the neonatal rat on day 2 after birth as designated by arrows a in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations